2004
DOI: 10.1037/0021-9010.89.6.1106
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Administrator-Witness Contact on Eyewitness Identification Accuracy.

Abstract: Concern that lineup administrators can influence eyewitness identifications has led researchers to suggest implementing double-blind testing, an idea that police resist. Using a typical eyewitness paradigm (video event followed by photographic identification test), the present study demonstrated that an alternative technique, minimizing the level of contact between lineup administrators and witnesses, could reduce false identifications without reducing hits. Specifically, witnesses were more likely to make dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(78 citation statements)
references
References 23 publications
(42 reference statements)
3
75
0
Order By: Relevance
“…The two studies showed similar patterns of results for simultaneous lineups, in that correct and false identification rates increased when suspect-specific bias was easier to convey and carry out. However, the proportional increases were not consistent across the two studies: Whereas Haw and Fisher (2004) showed an increase in innocence risk due to suspect-specific bias, Greathouse and Kovera (in press) showed a slight decrease in innocence risk. The results for sequential lineups were also inconsistent and also showed opposite patterns for innocence risk (increased innocence risk for Greathouse and Kovera [in press], but decreased innocence risk for Haw and Fisher [2004]).…”
Section: Simultaneous and Sequential Lineupsmentioning
confidence: 82%
See 2 more Smart Citations
“…The two studies showed similar patterns of results for simultaneous lineups, in that correct and false identification rates increased when suspect-specific bias was easier to convey and carry out. However, the proportional increases were not consistent across the two studies: Whereas Haw and Fisher (2004) showed an increase in innocence risk due to suspect-specific bias, Greathouse and Kovera (in press) showed a slight decrease in innocence risk. The results for sequential lineups were also inconsistent and also showed opposite patterns for innocence risk (increased innocence risk for Greathouse and Kovera [in press], but decreased innocence risk for Haw and Fisher [2004]).…”
Section: Simultaneous and Sequential Lineupsmentioning
confidence: 82%
“…To date, there have been only two experiments (Greathouse & Kovera, in press;Haw & Fisher, 2004) in which these biases have been examined in both target-present and targetabsent lineups, and they have not presented a consistent pattern of results. Such results should present an interesting challenge for models, because the bias is not about whether to identify (which can be modeled as a simple larger for guilty suspects than for innocent suspects when the correct identification rate is high and the false identification rate is low in the simultaneous lineup condition (as it was in the studies listed above).…”
Section: Summary and Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative would be to use any nonconflicting detail mentioned in the descriptions (i.e., a comprehensive description). It is often difficult to determine how descriptions are combined when researchers fail to report how descriptions are obtained or produced (e.g., Clare & Lewandowsky, 2004 provided no LINEUP FAIRNESS MEASURES 7 information; Haw &Fisher, 2004 andRyan, 1993 indicated they constructed a general description). Thus, we examined whether lineup fairness measures vary based on the type of description presented to mock witnesses.…”
Section: Descriptionmentioning
confidence: 99%
“…Many have argued vociferously for the universal uptake of double-blind procedures in administering investigative line-ups in order to ameliorate influences subjected on witnesses that may compromise the integrity of identifications made [20,21,[32][33][34][35].…”
Section: Double-blind Procedures As a Safe-guard Against Administratomentioning
confidence: 99%